Ants visiting inflorescences of Actinocephalus polyanthus (Bong.) Sano (Eriocaulaceae) - Tânia Tarabini Castellani; Benedito Cortês Lopes; Karla Zanenga Scherer; Carlos Eduardo Cereto; Elise Lara Galitzki (Biotemas, 2013)
Plants from the family Eriocaulaceae have a secretion of nectar in floral structures which promotes insect visitation, including ants. This study evaluated the ant species visiting inflorescences of Actinocephalus polyanthus in coastal dunes in southern Brazil and it checked whether the richness and composition of the visiting assemblies differed between the female and male flowering phenophases, due to the greater supply of resources by male flowers. Comments on the resources used and the visiting behavior were also investigated. We found 15 ant species, belonging to 8 genera and 4 subfamilies. There was no difference with regard to richness and diversity of visiting species associated to the male or female flowering phenophase. However, there was a difference with regard to the similarity of these assemblies, due to the higher occurrence of Camponotus fastigatus in the female flowering. Most species registered belong to genera which, typically, use floral and extrafloral nectar as food resource or they are generalist. Brachymyrmex sp.1, Camponotus fastigatus, and Dorymyrmex sp. were observed with pollen stuck to their body, something which suggests a potential transportation of this pollen between flowers.